A proposal for the application of Servant Leadership in Student Affairs Deanship at King Saud University - Alshammari, Radhi Turki (Journal of Educational and Psychological Sciences, 2022)
The aim of the research was to monitor the experiences of some international universities in applying Servant leadership in Student Affairs Deanships at universities, to identify the requirements and difficulties of applying Servant leadership at Student Affairs Deanship at King Saud University, and to present a proposed Prospective for applying the Servant leadership at Student Affairs Deanship at King Saud University. The research used the analytical descriptive Approach due to its suitability for the subject matter of the study, where the research was limited to the application of Servant leadership in the doctrines of students' affairs through dimensions (conceptual skills, empowerment, attention to subordinates, helping subordinates develop and succeed). The theoretical study found a number of results, the most important of which are: a number of difficulties encountered in applying the Servant leadership to the Student Affairs Deanships in general and King Saud University in particular, including: No interactive work system and student density beyond absorptive capacity and the lack of technical and office equipment with good specifications and the need for professional development of the workforce and inadequate establishment of the information repository, Lack of training aimed at effective performance, disruption of incentive systems, Poor coordination, lack of effective leadership, inadequate organizational systems and performance measurement standards as well as the inflexibility of laws and regulations, the difficulty of measuring results and the increase in the number of beneficiaries of the Student Affairs Deanships and the diversity of their categories organizational structures and the lack of a description of the organizational competencies of the administrative units and the absence of complementarity and cooperation between units.In the light of the results of the research, a proposed Prospective was presented for applying Servant leadership in Student Affairs Deanships at King Saud University and various Saudi and Arab universities.
Keywords: Servant Leadership; Student Affairs Deanship; Higher Education